An efficient synthesis of novel spiroindenopyridazine-4H-pyran derivatives. (10th November 2017) - Bayat, Mohammad; Hosseini, Hajar
Abstract : A simple one-pot synthesis of diverse spiroindenopyridazine-4 H -pyrans in EtOH without any catalyst. Abstract : A convenient one-pot protocol was developed for the synthesis of spiro[indeno[2, 1- c ]pyridazine-9, 4′-pyran]-3′, 4-dicarbonitrile derivatives by the reaction of cyanoacetohydrazide, ninhydrin, malononitrile and various cyclic CH-acids under reflux condition in ethanol. No hazardous solvent or catalyst was used in this method. The main advantages of this procedure are the availability of starting materials, very high yields and easy purification.